2017
DOI: 10.1002/etc.3906
|View full text |Cite
|
Sign up to set email alerts
|

Exposure effects of levonorgestrel on oogenesis in the fathead minnow (Pimephales promelas)

Abstract: The synthetic progestin levonorgestrel is commonly utilized in human oral contraceptives. It enters the environment as a component of wastewater treatment plant effluent, and has been measured at low ng/L concentrations in surface waters. It has been shown to activate fish androgen receptors, causing the physical masculinization of females, changes in reproductive behavior, and decreases in fecundity. In the present study, the effects of levonorgestrel exposure on early-stage oogenesis in the fathead minnow (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Over time, several generations of progestins have been developed, and are loosely classified based on the parent compound from which they are derived [5]. Laboratory exposure studies have recorded several effects associated with progestin exposure on reproduction in multiple fish species, including the masculinization of female fathead minnows [8,9] and eastern mosquitofish [10,11], changes to blood plasma sex steroid concentrations in the fathead minnow [9] and the common roach [12], decreased fecundity in the fathead minnow and Japanese medaka [8,9,13], alterations in normal reproductive behavior in the fathead minnow [8] and eastern mosquitofish [11], and decreased latestage oogenesis in female fathead minnows [14]. However, certain progestins (e.g., levonorgestrel and gestodene) have been shown to strongly bind and activate androgen receptors in the fathead minnow [2] and the Murray-Darling rainbowfish [7] with little to no activation of nuclear progesterone receptors, suggesting that some of the effects that are observed after exposure are controlled via androgen receptor-mediated pathways.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over time, several generations of progestins have been developed, and are loosely classified based on the parent compound from which they are derived [5]. Laboratory exposure studies have recorded several effects associated with progestin exposure on reproduction in multiple fish species, including the masculinization of female fathead minnows [8,9] and eastern mosquitofish [10,11], changes to blood plasma sex steroid concentrations in the fathead minnow [9] and the common roach [12], decreased fecundity in the fathead minnow and Japanese medaka [8,9,13], alterations in normal reproductive behavior in the fathead minnow [8] and eastern mosquitofish [11], and decreased latestage oogenesis in female fathead minnows [14]. However, certain progestins (e.g., levonorgestrel and gestodene) have been shown to strongly bind and activate androgen receptors in the fathead minnow [2] and the Murray-Darling rainbowfish [7] with little to no activation of nuclear progesterone receptors, suggesting that some of the effects that are observed after exposure are controlled via androgen receptor-mediated pathways.…”
Section: Introductionmentioning
confidence: 99%
“…However, certain progestins (e.g., levonorgestrel and gestodene) have been shown to strongly bind and activate androgen receptors in the fathead minnow [2] and the Murray-Darling rainbowfish [7] with little to no activation of nuclear progesterone receptors, suggesting that some of the effects that are observed after exposure are controlled via androgen receptor-mediated pathways. Although several studies have examined the impacts of progestin exposure on female ex vivo ovarian steroid production [16], vtg1 messenger ribonucleic acid (mRNA) expression [17,18], plasma estradiol (E2) concentrations [12,13], and oogenesis [14,18] in several fish species, few studies have focused on the alteration in male reproductive fitness due to changes in behavior and gamete quality. When triads composed of 1 male and 2 female fathead minnows were exposed to gestodene [8] and levonorgestrel [15], females began to exhibit masculinized behavior after just 24 h of exposure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, a number of studies had reported that P4 and synthetic progestins at low concentrations could cause reproductive endocrine disruption in fish. 5,[16][17][18][19][20][21][22][23][24][25] For instance, exposure to norethindrone at the juvenile stage could affect gonad differentiation and the sex ratio, which might be attributed to alterations in the transcriptional expressions of genes along the hypothalamic-pituitary-gonadal (HPG) axes. 20 Furthermore, 17α-ethynylestradiol can disrupt sexual differentiation, gonadal development, and reproduction in aquatic species.…”
mentioning
confidence: 99%